Cholesterol Levels In Bligon Goats During Estrous Cycle - Nadia Kartikasari; Risa Ummami (Jurnal Sain Veteriner, 2014)
The study was aimed to assess the status of cholesterol levels during the estrous cycle in goats. The present study was conducted by using 4 female cycling bligon goats (Capra hircus), aged 2-3 years, weighed 27-45 kgs, and clinically healthy and Venous blood sampling was done on days 1 (estrus), 3-4 (early luteal), 10-16 (late luteal), 17-20 (proestrus) using a syringe and collected in tubes containing lithium heparin. Plasma wasseparated by centrifugation, put into 1.5 ml Eppendorf tube and stored at a temperature of -20° C until analysis performed. Cholesterol levels were measured by using spectrophotometric method. Cholesterol concentrations during the estrous cycle were analyzed by General Linear Model Repeated Measure. The average of cholesterollevels in bligon goats is 52.20 ± 11.11 – 64.50 ± 18.46 mg/dl. The results showed that the concentration of cholesterol was between phases during the estrous cycle was not significantly different (P>0.05). However, there was a decreasing tendency of cholesterol concentration at the early luteal phase (52.20 mg/dl) and at the late luteal (53.19 mg/dl) compared to the levels at the follicular phase (65.50 mg / dl at estrus and 59.22 mg / dl at proestrus ). It can be concluded that the plasma level of cholesterol does not change significantly during theestrous cycle.